The Role of Tourism Accounting in The Context of Sustainable Tourism - Imansari, Lisa Cahyani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
Sustainable tourism as a development concept for sustainable tourism that can provide long-term impacts. Beyond just offering entertainment, sustainable tourism is expected to have positive impacts on the environment, social, cultural, and broader economic aspects for both the local community and visiting tourists. The purpose of this research is to examine and analyze the role of Tourism Accounting in supporting the success of Sustainable Tourism, with a case study on Rembangan Tourism in Jember. This research is based on a qualitative perspective or paradigm using a case study design. The results of this research show that tourism accounting in Rembangan Tourism has provided significant support in meeting the criteria for sustainable tourism.